PENGEMBANGAN MODEL MANAJEMEN PEMBELAJARAN BERBASIS TIK DI SEKOLAH DASAR - Maria, Edna; Sediyono, Eko (Universitas Kristen Satya Wacana, 2017)
The aim of this study isÂ to develop model of ICT-based learning management. With this tools and model, school can be easily monitor and evaluate the educational process. This research done by Research and Development (R&D). The place of the research is at SD Kristen Satya Salatiga, and data collection used interviews, observation and documentation. The data were analyzed using descriptive analysis and triangulation technique to test data validation. The result of the research are: The first step is Decision Making of ICT-based Learning, The second step is Planning of ICT-based Learning, The Third step is Implementation of ICT-based Learning, The Fourth step is Evaluation of ICT-based Learning. The key success factor of this model is on the second step that is how the teachers make the lesson plans and cooperate with all the parties related to the ICT-based learning management.